Hubungan Pengetahuan Dengan Perilaku Penggunaan Alat Pelindung Diri (APD) Pada Pekerja Proyek “Mainline 1” PT. Nindya Citra Kharisma Kso Tahun 2023 - Ferlina Rizky Indah Nugroho; Anggun Nabila; Namira Wadjir Sangadji; Putri Handayani (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Based on accident statistics data at PT. Nindya Citra Kharisma KSO, many accident cases are due to poor behavior in the use of Personal Protective Equipment (PPE) caused by low knowledge about PPE. Therefore, quantitative research was conducted on the relation of knowledge with the behavior of using Personal Protective Equipment (PPE) in workers of the "Mainline 1" project of PT. Nindya Citra Kharisma KSO in 2023. . This research is a quantitative research with an analytical descriptive design with a cross sectional method. The population in this study was 60 workers. In data collection using total sampling, then the data obtained is analyzed to describe relationships and images using the chi square test. Based on the results of the study, it is known that 65.5% have bad knowledge, show behavior in the use of bad personal protective equipment with a p-value of 0.050, meaning that there is a relation between knowledge and the behavior of using Personal Protective Equipment (PPE) with a Prevalence Ratio (PR) of 1.966. Researchers suggest that HSE is advised to reinforce the Tool Box Talk schedule, require workers to follow TBT and be present on time and provide strict sanctions if workers are absent or arrive late 3 times in a row.